2011
DOI: 10.2147/ndt.s12769
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for treatment-resistant schizophrenia

Abstract: Schizophrenia is a disabling mental illness with a lifetime prevalence of 0.7% worldwide and significant, often devastating, consequences on social and occupational functioning. A range of antipsychotic medications are available; however, suboptimal therapeutic response in terms of psychotic symptoms is common and affects up to one-third of people with schizophrenia. Negative symptoms are generally less amenable to treatment. Because of the consequences of inadequate symptom control, effective treatment strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 103 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…While current medications for schizophrenia work primarily by blocking D 2 -type dopamine receptors ( Kapur et al, 2000 ; McIlwain et al, 2011 ), recent theories suggest that abnormalities in glutamatergic neurotransmission may underlie the deteriorating course of schizophrenia, ultimately leading to dopaminergic dysregulation ( Olney and Farber, 1995 ; Sharp et al, 2001 ). The N -methyl d -aspartate (NMDA) receptor model suggests that hypofunctioning of these receptors in gamma-aminobutyric acid (GABA) interneurons causes a paradoxical, compensatory increase in presynaptic glutamate (Glu) release while GABA synthesis and release is downregulated ( Lisman et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…While current medications for schizophrenia work primarily by blocking D 2 -type dopamine receptors ( Kapur et al, 2000 ; McIlwain et al, 2011 ), recent theories suggest that abnormalities in glutamatergic neurotransmission may underlie the deteriorating course of schizophrenia, ultimately leading to dopaminergic dysregulation ( Olney and Farber, 1995 ; Sharp et al, 2001 ). The N -methyl d -aspartate (NMDA) receptor model suggests that hypofunctioning of these receptors in gamma-aminobutyric acid (GABA) interneurons causes a paradoxical, compensatory increase in presynaptic glutamate (Glu) release while GABA synthesis and release is downregulated ( Lisman et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 Clozapine is a tricyclic dibenzodiazepine, which is considered to be remarkably efficient in the treatment of schizophrenia, specifically in treatment-resistant schizophrenia. 3 Clozapine is metabolized by the cytochrome P450 (CYP) system of enzymes in the liver, yielding a pharmacologically active metabolite, norclozapine. The most influential CYP isoformin on clozapine metabolism is CYP1A2, which has a major impact on the determination of the dose of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, clozapine is prescribed to lessen the risk of recurrent suicidal behavior in schizophrenic patients. 3 The occurrence of extrapyramidal adverse events is considered rare with clozapine therapy. However, clozapine is sometimes limited to cases of treatment-resistant schizophrenia, as a result of its significant risks.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, the use of clozapine is usually reserved for those patients who do not respond adequately to previous trials of other antipsychotic medications 2. The therapeutic efficacy of clozapine is reported to be higher than that of other antipsychotics and the side effects reported are also higher 3. Various studies showed that the prevalence of metabolic syndrome among subjects taking clozapine was much higher than that of the subjects taking other antipsychotics 4.…”
Section: Introductionmentioning
confidence: 99%